Pengaruh Kemampuan Komunikasi Pimpinan terhadap Kinerja Pegawai Dinas Pariwisata - Robeet Thadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT The purpose of this study was to determine the effect of leadershipcommunication skills on the performance of the employees of the South Bengkulu Regency Tourism Office.The method in this study uses a quantitative approach, with explanatory research methods. The results showed that the leadership's communication skills had a positive and significant effect on the performance of the Tourism Office. It can be seen from the results of the regression test that the equation Y = 9.391 + 0.592X, this equation has a meaning, that the regression coefficient value of the leadership communication ability variable is 0.592 which is positive. The conclusion of the study is that improving the leader's communication skills will improve employee performance on work. Keywords: Employee Performance, Leadership Communication.